A supervised learning approach by machine learning and deep learning algorithms to predict type II DM risk - Farabe, Abdullah Al; Sharika, Tarin Sultana; Raonak, Nahian; Ashraf, Ghalib (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2019.